SPEAKING IN TONGUES: A REPORT ON THE SECOND MARXISM AND PSYCHOLOGY CONFERENCE, Morelia, Mexico, 9-11 August 2012 - Painter, Desmond (PINS-Psychology in Society, 2025)
“There was music in the cafes at night and revolution in the air.” So sings Bob Dylan in his classic 1975 song, Tangled up in blue. When asked by colleagues and friends about my experience of the Second Marxism and Psychology Conference, held in Morelia, Mexico, in August 2012, I often wish I could just quote these words by Dylan and be done with it. Unfortunately, things are not as simple, not even at a conference explicitly devoted to Marxism. Music there was aplenty; this was, after all, an international academic conference in an exotic location, an opportunity for campusweary academics to bust out a bit. But revolution? In the bar below my hotel room in central Morelia, a young singer delivered his nightly laments: beautiful cover versions of songs by Cuban troubadour Silvio Rodríguez. “Brillante exposición de modas, la desilusión” – Silvio on the disillusionments of life during the “Special Period” in post-revolutionary, post-Cold War Cuba …